Analisis Kinerja Sistem Antrian Pelanggan Menggunakan FIFO dan Parallel Processing pada Warung Ayam Pecak - Dhafa Hibrizi Sitorus; Dewi Aulia Tanjung; Ravil Baadilahasan Hrp; Chairil Umri (Universitas Islam Negeri Sumatera Utara, 2026)
This study analyzes the customer queuing system at Warung Ayam Pecak by applying the First In First Out (FIFO) method combined with parallel processing to improve service efficiency. The selection of this topic is based on the problem of relatively long customer waiting times due to the sequential service process. Data collection was conducted through field observations to obtain patterns of customer arrivals, service duration, and cooking time under initial conditions using only one stove and one kitchen worker. Next, a simulation model was developed to compare the initial system with the proposed system, which implemented two parallel cooking processes. The simulation results showed that the application of parallel processing was able to reduce the Average Waiting Time (AWT) from 25 minutes to 2.82 minutes and the Average Waiting Process (AWP) from 11.82 minutes to 6.2 minutes. These findings indicate that the addition of simple resources, in the form of one stove and one worker, can significantly increase service throughput and reduce queue length. This study concludes that queue system optimization through the FIFO and parallel processing approaches is effective in improving the operational performance of small-scale culinary businesses.Keywords: Queue simulation, FIFO, Parallel Processing, Waiting Time, Operational Efficiency